Adsorption of COD in Coking Wastewater on Nitric Acid-Modified Blue Coke Activated Carbon. (6th December 2019) - Jiang, Xu; Lan, Xinzhe; Song, Yonghui; Xing, Xiangdong
Abstract : The blue coke activated carbon (BAC) modified by nitric acid at different concentrations was used as an adsorbent to remove COD from coking wastewater. Characterization of BAC was performed using N2 adsorption/desorption techniques, scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), and Boehm titration. The results showed the Brunner–Emmet–Teller (BET) specific surface area and iodine value of BAC became higher after modification, and the adsorption capacity of BAC for coking wastewater was effectively improved with nitric acid modification. The optimal nitric acid concentration for modification was 3 mol/L (BAC-N3), which had more acid functional group contents than unmodified. The chemical oxygen demand (COD) removal rate was to reach 77.05% when 4 g BAC-N3 was added into 50 mL coking wastewater in 120 min with a shaking speed of 100 rpm at 25°C. Langmuir model could better describe equilibrium adsorption data by BAC-N3, and the kinetic study showed that the adsorption process was best fitted by the pseudo-second-order kinetic model.